Patterns of Neonatal Admission and Outcome in Neonatal Intensive Care Unit of a Tertiary Care Hospital (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Analyzing the neonatal admission pattern helps the policymakers to make better strategies for healthcare provider to deliver better service.Objective: To demonstrate the admission pattern and outcome of patients in the Neonatal Intensive Care Unit (NICU) in a tertiary care hospital of Bangladesh.Materials and Methods: This retrospective descriptive study was conducted on all neonates admitted to the NICU of Combined Military Hospital (CMH), Dhaka from January to December 2015. Data were collected from file records of the patients regarding age, gender, mode of delivery, working diagnosis, length of stay in NICU and immediate outcome.Results: A total of 502 neonates were admitted during the study period. Majority of the patients (77.3%) were admitted on the 1st day of life. There were 279(55.6%) males with a male to female ratio 1.2:1. The major cause of admission was prematurity (23.1%) and other leading causes were birth asphyxia (BA)14.9%, infant of a diabetic mother (IDM) 13.5%, neonatal sepsis 12.5%. Most of the neonates (82.7%) were delivered by caesarean section. About 84.1% were discharged after improvement, 65(12.94%) died and 15(3%) were referred to other specialties for further management. Within the first 24 hours of admission, 9.4% deaths occurred and two common causes of neonatal death were preterm (49.18%) and birth asphyxia (23%).Conclusion: Good outcome of a neonate depends on adequate management, monitoring and good nursing care in an intensive care unit. By paying good attention to perinatal services and improving the facilities in the unit, morbidity and mortality in neonates can be reduced.Journal of Armed Forces Medical College Bangladesh Vol.13(2) 2017: 49-53